2009
DOI: 10.1074/jbc.m109.048058
|View full text |Cite
|
Sign up to set email alerts
|

Silencing Mitogen-activated Protein 4 Kinase 4 (MAP4K4) Protects Beta Cells from Tumor Necrosis Factor-α-induced Decrease of IRS-2 and Inhibition of Glucose-stimulated Insulin Secretion

Abstract: Obesity and type 2 diabetes present partially overlapping phenotypes with systemic inflammation as a common feature, raising the hypothesis that elevated cytokine levels may contribute to peripheral insulin resistance as well as the decreased beta cell functional mass observed in type 2 diabetes. In healthy humans, TNF-␣ infusion induces skeletal muscle insulin resistance. We now explore the impact of TNF-␣ on primary beta cell function and the underlying signaling pathways. Human and rat primary beta cells we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
51
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 53 publications
8
51
0
Order By: Relevance
“…silencing has reproduced that reported earlier in rat primary ␤-cells (30). MafA is a highly phosphorylated protein and tightly controlled by the coordinated action of multiple kinase pathways (36 -39).…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…silencing has reproduced that reported earlier in rat primary ␤-cells (30). MafA is a highly phosphorylated protein and tightly controlled by the coordinated action of multiple kinase pathways (36 -39).…”
Section: Discussionsupporting
confidence: 67%
“…Of interest, knockdown of MAP4K4 by siRNA prevented the inhibitory effect of TNF-␣ on IRS2 expression in Min6 cells (Fig. 6C), an observation consistent with a previous study in rat primary islets (30). Taken together, the data presented here demonstrated unequivocally that MAP4K4 negatively regulates insulin gene transcription and signaling and that silencing of MAP4K4 essentially mimicked miR-30d-targeted down-regulation of MAP4K4 in protecting ␤-cells from TNF-␣-induced inhibition.…”
Section: Tnf-␣-induced Map4k4 Inhibits Insulin Genesupporting
confidence: 75%
“…Other studies have shown that Akt activity can be inhibited by proinflammatory cytokines (42,43). We therefore examined whether TRB3 knockdown attenuated the ability of cytokines to inhibit Akt Ser 473 phosphorylation (Fig.…”
Section: Figure 2 Mlk-dependent Induction Of Proapoptotic Markers Inmentioning
confidence: 99%
“…M itogen-activated protein kinase kinase kinase kinase 4 (MAP4K4, or HGK), and its homologues Misshapen and MIG-15 have been shown to regulate a multitude of biological processes, including embryonic development, 1,2 metabolism, 3,4 inflammation, 5 neural regeneration, 6 angiogenesis, 7 and cancer. 8,9 Given its diverse roles in these processes, we became interested in the therapeutic potential of MAP4K4 inhibition and began an endeavor to identify an inhibitor that would function in vivo.…”
mentioning
confidence: 99%